Bacterial and fungal microflora in surgically removed lung cancer samples - Apostolou, Panagiotis; Tsantsaridou, Aggeliki; Papasotiriou, Ioannis; Toloudi, Maria; Chatziioannou, Marina; Giamouzis, Gregory (Journal of cardiothoracic surgery, 2011)
Background Clinical and experimental data suggest an association between the presence of bacterial and/or fungal infection and the development of different types of cancer, independently of chemotherapy-induced leukopenia. This has also been postulated for the development of lung cancer, however the prevalence and the exact species of the bacteria and fungi implicated, have not yet been described. Aim To determine the presence of bacterial and fungal microflora in surgically extracted samples of patients with lung cancer. Materials and methods In this single-center prospective, observational study, tissue samples were surgically extracted from 32 consecutive patients with lung cancer, and reverse-transcription polymerase chain reaction (RT-PCR) was used to identify the presence of bacteria and fungi strains. Results The analysis of the electrophoresis data pointed out diversity between the samples and the strains that were identified. Mycoplasma strains were identified in all samples. Strains that appeared more often were Staphylococcus epidermidis, Streptococcus mitis and Bacillus strains, followed in descending frequency by Chlamydia, Candida, Listeria, and Haemophilus influenza. In individual patients Legionella pneumophila and Candida tropicalis were detected. Conclusions A diversity of pathogens could be identified in surgically extracted tissue samples of patients with lung cancer, with mycoplasma strains being present in all samples. These results point to an etiologic role for chronic infection in lung carcinogenesis. Confirmation of these observations and additional studies are needed to further characterize the etiologic role of inflammation in lung carcinogenesis.